Spectrum of microbial flora in diabetic foot ulcers - Bansal Ekta; Garg Ashish; Bhatia Sanjeev; Attri A; Chander Jagdish (Wolters Kluwer Medknow Publications, 2008)
A prospective study was carried out on patients with diabetic foot lesions to determine their clinical characteristics, the spectrum of aerobic microbial flora and to assess their comparative in vitro susceptibility to the commonly used antibiotics. A total of 157 organisms (143 bacteria and 14 fungi) were isolated and an average of 1.52 isolates per case was reported. Polymicrobial infection was found in 35% of the patients. In this study, Pseudomonas aeruginosa among the gram-negative (22%) and Staphylococcus aureus among the gram-positive (19%) were the predominantly isolated organisms, while Candida was the most predominantly isolated fungus. Antimicrobial sensitivity pattern of the isolates is discussed in detail. There was a linear increase in the prevalence of organisms with increase in Wagner′s grade. Neuropathy (76%) and peripheral vascular disease (57.28%) was a common feature among the patients. Poor glycemic control was found in 67% of the patients. Awareness about lower limb complications of diabetes was very low (23%) among the patients